Dampak Gaji dan Gaya Kepemimpinan Terhadap Kepuasan Kerja Karyawan (Studi Kasus Pada PT Cipta Mandiri Agung Jaya) - Yuliana, Yuliana; Arwin, Arwin; Pratiwi, Jean Dwi (BISMA Cendekia, 2020)
The research aimed to know the impact of salary and leadership style on employee job satisfaction at PT. Cipta Mandiri Agung Jaya (CMAJ). The research method applied is the associative quantitative method. The research incorporates 2 types of data sources which are primary data and secondary data. The data collection method is done through the distribution of survey questionnaires to respondents. The total population consisted of 30 employees and all of them were taken as the sample. The data analysis method was done through a series of tests such as the Coefficient Determination Test (R2), F test, t-test, and Multiple Linear Regression. The result of the research showed that the test of the regression model of salary and leadership style variable on employee job satisfaction indicated Fcount 3,449 > Ftable 3,34. It can be concluded that the salary and leadership style has a positive impact on employee job satisfaction. Partially, salary has a positive influence on employee job satisfaction which can be seen from the tcount2,610> ttable2,052, which means that Ha is accepted. Meanwhile, leadership style has no impact on employee job satisfaction since the leadership style variable indicated a value of tcount 0,364<ttable2,052, which means Ho is accepted.